Pengaruh Model Pembelajaran Peer Lesson terhadap Kemampuan Procedural Fluency Matematika - Mailantri, Ismi; Putri, Rahmi; Sari, Maila; Ulandari, Nelpita (Edumatika, 2020)
This study aims to determine (1) the mathematical fluency procedural ability of students taught using the peer lesson learning model and those not taught with the peer lesson learning model in class VIII, and (2) the effect of the peer lesson learning model on the mathematics procedural fluency ability of grade VIII students . The population in this study was grade VIII students of SMP Negeri 11 Sungai Penuh, for the study sample consisted of 2 classes from 3 classes in the population, the samples in this study were taken by random sampling technique in which class VIII B was an experimental class and class VIII C was a control class. . Based on the results of research using the t-test for hypothesis testing, it was found that the peer lesson learning model affected the mathematical procedural fluency ability of students in class VIII.